Sports injuries according to the Functional Movement Screen (FMS) test among students of the Faculty of Physical Education and Sports Sciences – University of Samarra - Mohammed Abdulsalam Fadel Mahdi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aimed to identify the areas of the body most prone to sports injuries, as assessed by the Functional Movement Screen (FMS), among students at the Faculty of Physical Education and Sports Sciences at the University of Samarra. The researcher adopted a descriptive approach due to its suitability for the nature of the research. The study population consisted of third- and fourth-year male students at the Faculty of Physical Education and Sports Sciences – Samarra University for the academic year (2025–2026), numbering 253 students, whilst the research sample comprised 107 students selected using a purposive sampling method, representing 42.29% of the study population. The researcher used the Functional Movement Screen (FMS), which consists of seven basic movement tests, to assess the quality of basic movement patterns and identify movement imbalances that may increase the likelihood of sports injuries. The data were analysed using SPSS 24, relying on the mean, standard deviation, skewness coefficient and percentage. The study results revealed variations in the levels of functional movement patterns among the research sample; whilst most students achieved scores indicating an acceptable level of motor competence, whilst some results indicated deficiencies in certain basic movement patterns among a number of students, which may increase their susceptibility to sports injuries whilst engaging in physical activities. The study concluded that the Functional Movement Screen (FMS) is an effective tool for detecting movement imbalances and identifying areas of weakness in the students’ musculoskeletal system, which contributes to improving the quality of motor performance and reducing the risk of sports injuries. The study recommended that the Functional Movement Screen (FMS) be adopted as a routine method for assessing movement patterns among physical education students, and that corrective training programmes be designed to improve motor efficiency and reduce the risk of sports injuries.